GRADOS DE SATISFACCION CON LOS DIFERENTES ASPECTOS DE LA VIDA UNIVERSITARIA - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2010)
Abstract. Study on the degree of satisfaction regarding academic environment in the university life of the students of the Faculty of Social and Human Sciences University of Antioquia. Realized in 1999, like methodological practice of the students of the courses of Quantitative Methods I and II. of the Program of Sociology. Dimension: the satisfaction with respect to a set of variables like degree of satisfaction regarding the non-academic services in the University according to academic Department. Degree of satisfaction with institutional mass media. Images about the academic works in the University. The services that the Faculty offers to its students Appreciation of the students about the demands of academic work. Student´s satisfaction with campus spaces. Opinion on the educational performance. Evaluation on the educational performance according to academic program. Appreciation on situations of conflicts between students and professors. Expectations and appreciations on curricular activities extra programmed by the Department or Faculty student expectations by activities that had to program the academic Faculty. Appreciation on the future professional. Appreciation on field in which it would like to carry out its work like professional. Dimension: the satisfaction with respect to a set of variables: Degree of satisfaction with the non-academic services in the University according to academic program. Degree of satisfaction with institutional mass media. Images about the academic works in the University. The services that the Faculty offers to its students Appreciation of the students about the demands of academic work. Student´s satisfaction with campus spaces. Opinion on the educational performance. Evaluation on the educational performance according to academic program. Appreciation on situations of conflicts between students and professors. Expectations and appreciations on curricular activities extra programmed by the Department or Faculty student expectations by activities that had to program the academic Faculty. Appreciation on the future professional. Appreciation on field in which it would like to carry out its work like professional. Resumen. Estudio de los grados de satisfacción con los diferentes aspectos de la vida universitaria de los estudiantes de la Facultad de Ciencias Sociales y Humanas de la Universidad de Antioquia realizado el año 1999, como práctica de 2 los estudiantes del curso de Diseños Cuantitativos I y II. Del Programa de Sociología Se mide la satisfacción respecto a un conjunto de variables Grado de satisfacción con la oferta extraacadémica en la Universidad según programa académico Grado de satisfacción con los medios de comunicación estudiantil e institucionales. Imágenes acerca de la cotidianidad académica en la Universidad los servicios que ofrece la facultad a sus estudiantes Apreciación de los estudiantes acerca de las demandas de trabajo académico. Grado de satisfacción del estudiante de la facultad con sus espacios físicos Imágenes sobre el desempeño docente Evaluación sobre el desempeño docente porcentajes de calificaciones de 4 o más según programa académico Apreciación sobre situaciones de conflictos entre estudiantes y profesores Expectativas y apreciaciones sobre actividades extra curriculares programadas por el programa o facultad expectativas estudiantiles por actividades que debieran programar la facultad o sus programas académicos Apreciación sobre el futuro profesional Apreciación sobre posibilidades de empleo en el futuro Apreciación sobre campo en el que le gustaría realizar su trabajo como profesional.